2011
DOI: 10.1369/0022155410394859
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C4.4A, a Structural uPAR Homolog, Reflects Squamous Epithelial Differentiation in the Adult Mouse and during Embryogenesis

Abstract: The glycosylphosphatidylinositol (GPI)–anchored C4.4A was originally identified as a metastasis-associated protein by differential screening of rat pancreatic carcinoma cell lines. C4.4A is accordingly expressed in various human carcinoma lesions. Although C4.4A is a structural homolog of the urokinase receptor (uPAR), which is implicated in cancer invasion and metastasis, no function has so far been assigned to C4.4A. To assist future studies on its function in both physiological and pathophysiological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 38 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…In this study, we investigated the localization of C4.4A in the progression from normal bronchial epithelium, to basal cell hyperplasia, squamous metaplasia, dysplasia, CIS, and ultimately invasive SCC, as well as from normal alveolar epithelium to invasive AC, through the stages of AAH and BAC. Normal expression of C4.4A in stratified squamous epithelia is stringently regulated, as typified by its confinement to the squamous side of squamo‐columnar junctions 9. In line with this, the present study reveals a clear difference between invasive SCC and AC, with the former generally being positive and the latter negative for C4.4A.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we investigated the localization of C4.4A in the progression from normal bronchial epithelium, to basal cell hyperplasia, squamous metaplasia, dysplasia, CIS, and ultimately invasive SCC, as well as from normal alveolar epithelium to invasive AC, through the stages of AAH and BAC. Normal expression of C4.4A in stratified squamous epithelia is stringently regulated, as typified by its confinement to the squamous side of squamo‐columnar junctions 9. In line with this, the present study reveals a clear difference between invasive SCC and AC, with the former generally being positive and the latter negative for C4.4A.…”
Section: Discussionsupporting
confidence: 86%
“…One such potential biomarker is the C4.4A protein,4, 5 which is a structural homologue to the urokinase‐type plasminogen activator receptor 6. Expression of C4.4A in normal tissues is mostly found in suprabasal layers of squamous epithelium such as the esophagus and skin,7–9 and it is thus absent from healthy lung tissue. C4.4A has, however, been reported to be upregulated in lung tumor tissue,5, 10 and we have recently shown that C4.4A has a pronounced prognostic impact in NSCLC, primarily ascribed to a severely compromised overall survival of adenocarcinoma (AC) patients with high C4.4A expression 11…”
mentioning
confidence: 99%
“…Immunohistochemical staining was performed as previously described (Kriegbaum et al 2011). In brief, 3-µm sections were deparaffinized and pre-treated with Proteinase K for 15 min at 37C for antigen retrieval of C4.4A and CK1 (10 µg/ml Proteinase K) and Haldisin (5 µg/ml Proteinase K).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In comparison, age-and genetically matched embryos with no TAM treatment (Figure 5d,e) showed no significant mG labeling. It is worth noting that mouse embryo vibrissal development starts around E14.5-E15.5 (Davidson & Hardy, 1952;Kriegbaum, Jacobsen, Hald, & Ploug, 2011). Although oxygen concentrations of fetal mouse skin have not been directly examined, both physical hypoxia (pO 2 = 2.4 mmHg) and HIF-1α protein are observed in fetal sheep skin at Gestation Day 100 (Scheid et al, 2002) that is similar to mouse E13-14.…”
Section: Validation Of the In Vivo Hypoxia-sensing Ability Of The Rmentioning
confidence: 99%